PhoenixFire
  • PhoenixFire
Prove by induction that \[(A_1A_2...A_n)^{-1}={A_n}^{-1}...{A_2}^{-1}{A_1}^{-1} \]\[\forall n\in \mathbb{N}\] and A_i for i=1, 2, ... are invertible matrices of same dimensions
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
PhoenixFire
  • PhoenixFire
Base step: Let n=1 \[(A_1)^{-1}=A_1^{-1}\]\[A_1^{-1}=A_1^{-1}\] Inductive Hyp. : Assume the statement holds true for n=m for some m in Natural Numbers. Inductive Step: Let n=m+1\[(A_1A_2...A_mA_{m+1})^{-1}=A_{m+1}^{-1}A_m^{-1}...A_2^{-1}A_1^{-1}\]\[(A_1A_2...A_mA_{m+1})^{-1}=A_{m+1}^{-1}(A_1A_2...A_m)^{-1}\] That's about as far as I got. Something doesn't seem right, and the Inductive Step isn't making sense as I don't know how to continue.
UnkleRhaukus
  • UnkleRhaukus
*
experimentX
  • experimentX
write |dw:1349805212895:dw|

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

experimentX
  • experimentX
|dw:1349805366358:dw|
asnaseer
  • asnaseer
I would first show that: \((A_1A_2)^{-1}=A_2^{-1}A_1^{-1}\) Then I would assume it is true for n=k., i.e.: \((A_1A_2...A_k)^{-1}=A_k^{-1}..A_2^{-1}A_1^{-1}\) And finally I would show that this also leads to: \((A_1A_2...A_k A_{k+1})^{-1}=A_{k+1}^{-1}A_k^{-1}..A_2^{-1}A_1^{-1}\)
asnaseer
  • asnaseer
For the final step, you can use the hints given to you by @experimentX
asnaseer
  • asnaseer
Please let me know if you require any further explanation.
PhoenixFire
  • PhoenixFire
I will attempt this in a few hours again... I have to go into Uni right now.
asnaseer
  • asnaseer
ok - good luck! :)
PhoenixFire
  • PhoenixFire
Okay I have 2 questions now. 1) Could I not state that from my Inductive Hypothesis (the statement is true for n=k) and let \[B_1=(A_1A_2...A_k)\]\[B_2=A_{k+1}\] and then show: \[(A_1A_2..A_nA_{n+1})^{-1}=B_2^{-1}B_1^{-1}\] From Ind. Hyp. with an n=2 \[(A_1A_2..A_nA_{n+1})^{-1}=(B_1B_2)^{-1}\]And then substitute in B1 and B2 again to result in an equality of Left hand side and Right hand side? 2) If I choose my base step as n=2 and want to prove \[(A_1A_2)^{-1}=A_2^{-1}A_1^{-1}\]Could I use a direct proof: Multiply both sides by A1A2\[(A_1A_2)^{-1}A_1A_2=A_2^{-1}A_1^{-1}A_1A_2\]\[I=A_2^{-1}A_2\]\[I=I\]Proving it for n=2. Am I correct to do it in this way?
experimentX
  • experimentX
yeah you are correct ... you can use this law to show for n=3,4,... up to n
experimentX
  • experimentX
for the last step, assume it to be true upto n, show that it is true for n+1 then this must be true for any n inductively.
PhoenixFire
  • PhoenixFire
Excellent. I understand it now. Out of curiosity, is my direct proof also valid?
experimentX
  • experimentX
from this particular point, it's correct ... for n=2 2) If I choose my base step as n=2 and want to prove ------------
experimentX
  • experimentX
now show it for n=3 and n=4
PhoenixFire
  • PhoenixFire
Well for 3 and 4 I'd use pretty much the same direct proof to reduce it to an Identity on both side proving an equality.
experimentX
  • experimentX
yes you can do that ... let it assume to be true for some n. then show it to be true for n+1 ..... you can do this by assuming \( A_1 A_2 ...A_n = A\) so that \( A_1 A_2 ...A_n A_{n+1} = A\times A_{n+1}\) Now we assume \( (A_1 A_2 ...A_n)^{-1} = A_n^{-1} ...A_2^{-1}A_1^{-1} \) we show that \( (A_1 A_2 ...A_nA_{n+1})^{-1} = A_{n_+1}^{-1}A_n^{-1} ...A_2^{-1}A_1^{-1} \)
experimentX
  • experimentX
doing that will make your matrix simple product of two matrices. use the simple trick and assumption to show that property.
PhoenixFire
  • PhoenixFire
Great! Thank you for your help!
experimentX
  • experimentX
yw.

Looking for something else?

Not the answer you are looking for? Search for more explanations.